2014
DOI: 10.1155/2014/913932
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects in the BivalvePerna pernaandMytilus galloprovincialis: Impact on the Environment due to Contamination by Copper

Abstract: This work presents the study of the effects of acute exposure to various concentrations of copper from 0.03 to 0.59 mol⋅L −1 on the metabolic activities (nitrogen and phosphorus), protein levels, catalase (CAT) enzyme activities, and the biological response malondialdehyde (MDA) in the mollusks Perna perna and Mytilus galloprovincialis. The concentrations above 0.88 mol⋅L −1 have proven to be lethal to P. perna. The results show slight disturbances of metabolism as a result of pollutant and a significant corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Similar to our ndings, MDA concentration increases in the marine bivalve, Perna perna, only at low Cu concentration (Errahmani et al, 2014). The cellular stress of Cu is often apparent at low doses because of the reduced lysosomal stability in the exposed organisms (Svendsen and Weeks, 1997;Viarengo et al, 2000).…”
Section: Resultssupporting
confidence: 86%
“…Similar to our ndings, MDA concentration increases in the marine bivalve, Perna perna, only at low Cu concentration (Errahmani et al, 2014). The cellular stress of Cu is often apparent at low doses because of the reduced lysosomal stability in the exposed organisms (Svendsen and Weeks, 1997;Viarengo et al, 2000).…”
Section: Resultssupporting
confidence: 86%
“…The decrease of mussels' metabolism may be related to the capacity of bivalves to close their valves and reduce their filtration and respiration rates when exposed to contaminants (Gosling, 2003;Ortmann and Grieshaber, 2003). Previous studies also demonstrated that metals and metalloids even at lower exposure concentrations induced similar metabolic depression in bivalves (Errahmani et al, 2014;Liu et al, 2012;Velez et al, 2017). The present results also demonstrated that mussels exposed to As 1000 µg/L contaminated seawater strongly increased their antioxidant defences, which may result from the overproduction of reactive oxygen species due to the stress induced by As, which were efficient in limiting the occurrence of LPO.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In fact, temperature strongly influences the respiration rates (direct relation), the excretion rates (above 25 °C) and salinity is proved to have a strong influence on clearance rates, which are inhibited at low salinities [22,23]. Results of other studies of pH effects in bivalve molluscs showed that some deleterious effects set in at pH values around 7.5, and all studies show that marine bivalve molluscs cannot tolerate pH values ≤ 7.0 [24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…During the experimental period, temperature, pH and salinity have been constantly monitored in all the tanks to assess the quality of the waters and to evaluate the possible influence of environmental parameters on the physiology of organisms [23,49]. All parameters have been measured with a multiparametric probe YSI 85 System (YSI Incorporated,Yellow Spring, OH, USA) and a HI 83140 pH-meter (HANNA Instrument, Padova, Italy).…”
Section: Methodsmentioning
confidence: 99%